HUBUNGAN DUKUNGAN SOSIAL TERHADAP RESILIENSI KELUARGA DI MASA PANDEMI PADA RT 05 RW 08 KELURAHAN SALATIGA KECAMATAN SIDOREJO KOTA SALATIGA - Albertus Atalarico Krisna Herdianto; Ratriana Yuliastuti Endang Kusumiati (Jurnal Cakrawala Ilmiah, 2023)
Family resilience is important for every family to have, especially in an atmosphere of the Covid-19 pandemic. The main task of the family is to meet the physical, spiritual and social needs of all its members. The aim of the research is to find out the relationship between social support and family resilience during a pandemic. The data collection technique used in this study was to distribute questionnaires or questionnaires to respondents and by using a random sampling technique. The subjects who were the respondents of this study were the people in RT 5 RW 8 Salatiga Village, Sidorejo District, Salatiga City. Based on the results of the correlation test about the relationship between social support and family resilience that has been carried out, the results of the correlation between these variables produce a positive value. This shows that the relationship between social support and family resilience is positive. It can be seen from instrumental support 0.002 (p<0.05), self-esteem support 0.038 (p<0.05), belonging support 0.004 (p<0.05), while informational support has a significance value of 0.051 (p>0, 05), which means the results of the correlation value if there is a significant positive relationship to the form of social support, namely instrumental support, self-esteem support, and belonging support. Therefore, the social support that these residents have, the higher the family resilience experienced, and conversely, if the social support experienced by these residents is lower, the resilience of the family will be lower in residents of RT 5 RW 8, Salatiga District, Sidorejo Village, Kota Salatiga.